Effects of supplementation with acai ( Euterpe oleracea Mart.) berry-based juice blend on the blood antioxidant defence capacity and lipid profile in junior hurdlers. A pilot study - Sadowska-Krępa, E; Kłapcińska, B; Podgórski, T; Szade, B; Tyl, K; Hadzik, A (Biology of Sport, 2015)
The purpose of this pilot study was to examine whether regular consumption of an acai berry-based juice blend would affect sprint performance and improve blood antioxidant status and lipid profile in junior athletes. Seven junior hurdlers (17.5±1.2 years) taking part in a pre-season conditioning camp were supplemented once a day, for six weeks, with 100 ml of the juice blend. At the start and the end of the camp the athletes performed a 300-m sprint running test on an outdoor track. Blood samples were taken before and immediately after the test and after 1 h of recovery. Blood antioxidant status was evaluated based on activities of antioxidant enzymes (superoxide dismutase [SOD], catalase [CAT], glutathione peroxidase [GSH-Px], glutathione reductase [GR]), concentrations of non-enzymatic antioxidants (reduced glutathione [GSH], uric acid), total plasma polyphenols, ferric reducing ability of plasma (FRAP), thiobarbituric acid reactive substances (TBARS) and activities of creatine kinase (CK) and lactate dehydrogenase (LDH) as muscle damage markers. In order to evaluate potential health benefits of the acai berry, the post-treatment changes in lipid profile parameters (triglycerides, cholesterol and its fractions) were analysed. Six weeks’ consumption of acai berry-based juice blend had no effect on sprint performance, but it led to a marked increase in the total antioxidant capacity of plasma, attenuation of the exercise-induced muscle damage, and a substantial improvement of serum lipid profile. These findings strongly support the view of the health benefits of supplementation with the acai berry-based juice blend, mainly attributed to its high total polyphenol content and the related high in vivo antioxidant and hypocholesterolaemic activities of this supplement.